Preoperative brain temperature imaging on proton magnetic resonance spectroscopy predicts hemispheric ischemia during carotid endarterectomy for unilateral carotid stenosis with inadequate collateral blood flow. (3rd August 2018) - Tsutsui, Shouta; Nanba, Takamasa; Yoshioka, Yoshichika; Sasaki, Makoto; Fujiwara, Shunrou; Kobayashi, Masakazu; Yoshida, Kenji; Miyoshi, Kenya; Sato, Shinpei; Ogasawara, Kuniaki
Abstract: Objective Preoperative magnetic resonance (MR) angiography sometimes shows the absence of collateral flow via the circle of Willis. This study examined whether brain temperature (BT) imaging on multi-voxel proton MR spectroscopy after this finding increases the accuracy of predicting hemispheric ischemia during internal carotid artery (ICA) clamping during endarterectomy for patients with symptomatic unilateral carotid stenosis. Methods In 52 patients with ICA stenosis (≥70%) and absence of collateral blood flow via the circle of Willis on preoperative MR angiography, BT imaging was displayed using proton multi-voxel MR spectroscopy. The difference between BTs in the affected and contralateral hemispheres (BTaffected hemisphere  − BTcontralateral hemisphere ) in the deep white matter of the centrum semiovale was calculated and defined as hemispheric ΔBT. Development of cerebral hemispheric ischemia during ICA clamping was determined from intraoperative electroencephalography (EEG). Results Multivariate analysis revealed that high preoperative hemispheric ΔBT was significantly associated with development of EEG-defined hemispheric ischemia (95% confidence intervals [CIs], 5.376–15.452; p  = 0.006). The positive-predictive value for development of EEG-defined hemispheric ischemia was significantly greater for preoperative hemispheric ΔBT following preoperative MR angiography (95%CI, 42–87%) than for preoperative MR angiography alone (95%CI, 13–37%). Conclusions For patients without collateral flow via the circle of Willis, BT imaging increases the predictive accuracy for development of hemispheric ischemia during ICA clamping during CEA.